Innovation self-efficacy: The influences of management employee trust and organizational support - Lapuz, Mark Christopher (Animo Repository, 2021)
The purpose of this study is to determine the effect of organizational support and management employee trust on innovation self-efficacy among fast-moving consumer goods employees in Metro Manila. Out of 161 online questionnaires distributed, 100 were used in this study and were boot strapped to 3,000 respondents. Data were analyzed through partial least squares – structural equation modelling. Findings showed that organizational support and management employee trust directly influence an employee’s innovation self-efficacy with management employee trust as the more significant antecedent The research showed valuable guidance in implementing a supportive and trusting environment to aid employees boost their innovation self-efficacy.